About the new human rights: Following the assumption of artificial fertilization of women alone - Díaz de Terán Velasco, María Cruz (2019)
The article, following the thought of J. Ballesteros, carries out a reflection on the protection and the promotion of single maternity by assisted human reproduction, regulated by the Spanish Law. The reflection is made from a key aspect of legal anthropology, such as otherness, and the place it occupies in the task of finding the real meaning of Law.